Peranan Puskesmas dalam Menghadapi Keratitis Ulcerosa - A. Soemarsono, A. Soemarsono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
Keratitis ulcerosa is a common disease in Yogyakarta and surrounding: This disease will cause blindness without good and right management. Usually it is encountered in rural areas caused by mud or pin, some materials in the field, for example wood or leaf and other corpora aliena.When complication occurs, perforation happens, resulting in total blindness.The treatment is easy when administered immediately. Sometimes there are difficult cases of keratitis ulcerosa which are resistent to treatment and need referral to the eye hospital after simple treatment is found to be unsuccessful in one week. From data presented the simple treatment is successful enough.Key Words: keratitis ulcerosa - health center - blindness - hypopyon - Aureomonas hydrophila